الأنشطة اللغوية ودورها في ممارسة كلام الطلبة في معهد زيس العصري الإسلامي بتشيلونجوك بانيوماس جاوى الوسطى - Ade Ruswatie; Enjang Burhanudin Yusuf; Anwar Masduki (Fakultas Tarbiyah, Universitas Darussalam Gontor, 2024)
ZIIS Islamic Modern College is one of the Islamic modern educational institutions located in Banyumas, Central Java, which prepares its students for individual and social life. The institute holds various activities, including language activities. These language activities are organized by the college with the goal of habituating students to use language in their daily conversations. The aim of this research is to describe the role of language activities in practicing students' speech at ZIIS Islamic Modern College in Cilongok, Banyumas, Central Java. This research uses a qualitative approach with a field study design. The researcher employed interviews, observations, and document analysis to collect data. After conducting the research, the researchers obtained the following results: The language activities at ZIIS Islamic Modern College include vocabulary presentations, weekly conversations, lectures, watching movies, and inviting Arabic speakers. These activities play an important role. One of their roles is to practice students' Arabic and English speech, focusing on short daily expressions.